MODEL PENDIDIKAN KARAKTER DALAM MASYARAKAT JEPANG - Budi Mulyadi (Universitas Diponegoro, 2014)
Abstract This research entitled The Model of Character Education in Japanese society. The main goal of this research is to know how the model of character education in Japanase society is done. This research is combination between field and library research. Main methods are observation, interview, intepretation. There are unique character in Japanese society in which couldn’t be found in other nations. Spirit of Bushido (discipline, honest, tough, work hard) is foundations of Japanese character. This such a character building is deserve to become an example to Indonesia. Japan shows us, they build character successfully. Japan become a developed modern nation without losing their core values and cultural. Key word: Charakter Building, Japanese Society and culture, Bushido